Pengaruh Model Pembelajaran Problem Solving Berbantuan Media Simulasi Phet Terhadap Kemampuan Pemecahan Masalah Fisika - Halmuniati Halmuniati (Jurnal Penelitian Pendidikan Fisika, 2022)
The purpose of this study was to determine the effect of the problem solving learning model with the help of PhET simulation media on students' ability to solve physical problems. This research was conducted at SMAN 2 Parigi, Muna Regency in the 2021/2022 academic year. The approach used is the quasi-experimental method. The sampling technique was purposive sampling so that the experimental class was obtained, namely XI MIA 3 and the control class XI MIA 2. The design used was Non-equivalent control design pretest-posttest. The instrument used is a description of the questions as many as 10 questions to measure the ability to solve problems. The data analysis technique used was the ANOVA test through SPSS 21. Based on the results of the research that had been done, it was found that the PhET media-assisted problem solving learning model had a significant influence on students' physical problem solving abilities as seen from the sig. < 0.05.